Neoarchean-Paleoproterozoic terrane assembly and Wilson cycle in the North China Craton: an overview from the central segment of the Trans-North China Orogen - Tang, Li; Santosh, M. (Earth-science reviews, 2018)
The North China Craton (NCC) is one of the important Precambrian nuclei of the globe as well as an integral component of the Paleoproterozoic supercontinent Columba. The NCC is considered in popular models as an assembly of two major crustal blocks, the Eastern and Western Blocks, which were sutured along the Trans-North China Orogen (TNCO), which represents a major Paleoproterozoic collisional orogen. The central segment of the TNCO preserves important keys to unravel the tectonic history of amalgamation and cratonization of the NCC. Here we present an overview on the lithology, geochemistry, geochronology, Lu-Hf isotopes and metamorphic history of the Neoarchean to Paleoproterozoic rocks in the major basement terranes from the central segment of the TNCO. The available data allow us to re-construct the major Precambrian events from the heart of the NCC as follows. (1) 2.58–2.48 Ga: amalgamation of three microblocks (Ordos, Qianhuai and Xuchang) along the Wutai granite-greenstone belt and its branch at the Zanhuang area, together with the convergence of major microblocks along other ~2.5 Ga granite-greenstone belts leading to the initial cratonization of the NCC. (2) 2.50–2.45 Ga: post-collisional extension as represented by undeformed mafic dykes and granitoid dykes or plutons, resulting in the opening of an oceanic basin along the Hengshan and Huai’an-Xuanhua Complexes. (3) 2.45–2.12 Ga: subduction in the Hengshan, Huai’an-Xuanhua and Lüliang Complexes, and simultaneous rifting in the Fuping, Wutai and Zanhuang Complexes. (4) 2.12–1.98 Ga: opening of oceanic basins in the Wutai and Fuping areas followed by double subduction of the oceanic lithosphere and arc magmatism in the Fuping, Wutai and Lüliang Complexes, with coeval rifting in the northern part as represented by the Hengshan and Huai’an-Xuanhua Complexes and the southern side as represented by the Zanhuang Complex. (5) 1.96–1.80 Ga: the assembly of the separated terranes (or complexes) driven by the amalgamation of the Western and Eastern Blocks. The collisional event may have occurred at 1.96–1.90 Ga, and the 1.88–1.80 Ga metamorphic ages might represent the retrograde cooling during exhumation. (6) Termination of the collisional event represented by post-collisional intrusions of granitoids, charnockites and pegmatites until ca. 1.74 Ga. Thus the central segment of the TNCO records a prolonged Wilson cycle following the initial cratonization of the NCC during Neoarchean, and involved multiple rift-subduction and collisional processes in the Paleoproterozoic resulting in the unified NCC and its incorporation into the supercontinent Columbia. [Display omitted] •Initial cratonization of the North China Craton occurred at 2.58–2.48 Ga.•Post-collisional magmatism during 2.5–2.45 Ga resulted in the opening of oceanic basin.•Subduction-rift system I (2.45–2.12 Ga) and II (2.12–1.98 Ga) formed various arc- and rift-related rocks.•The terrane assembly and collision between the Eastern and Western Blocks occurred at 1.96–1.90 Ga.